A Rare Case of Midostaurin-Associated Sweet's Syndrome. (22nd April 2022) - Yasin, Hesham; Laytem, Tessa; Sutamtewagul, Grerk; Ayyappan, Sabarish
Abstract : Acute febrile neutrophilic dermatosis which is referred as Sweet's syndrome (SS) is a dermatological condition characterized by fever, erythematous rash, and leukocytosis. SS can be idiopathic or associated with malignancies or medications. We present a rare case of SS which developed shortly after starting midostaurin in a patient with acute myelogenous leukemia (AML).